Method of Printing Carved on Wood under the Nguyen Dynasty of Vietnam: Study of Woodblocks Recognized by UNESCO as a World Documentary Heritage - Hang, Le Thuy; Van, Vu Hong (International Journal of Psychosocial Rehabilitation, 2020)
At present, in Vietnam, there is still no full awareness of woodblocks in the Nguyen Dynasty. Although the Nguyen Dynasty woodblocks have been UNESCO recognized as a world documentary heritage site, few people know about them. The debate revolves around the stages to create woodblocks, tools used by artisans to sculpt on wooden boards, how to sculpt on these boards, how to deal with wooden planks so they can endure over time, how to print from wood to paper onto paper, etc. This study focuses on explaining the issues just mentioned at the same time making some comments about the values that it has been in history in general and the printing history of Vietnam in particular.